Entre o estranho e o afeto: construção de sentidos sobre as relações de amizade entre travestis - Rocha, Rita Martins Godoy (2011)
In the field of humanities discipline, we identified that productions are incipient in the world of transvestites. The research that has addressed this issue is primarily anchored in anthropology, highlighting the ethnographic research that reflect the daily lives of transvestites and describe their lifestyles. These productions have emphasized many times, the world of transvestites practices associated with prostitution, recognizing this kind of work as an important means for the construction of sociability. Considering the possibility of recognizing other views, links and spaces that involve the complexity of this universe, this study aims to describe the interpretative repertoires on the relations of friendship between the transvestites. The participants of this study are 10 transvestites who live in Uberlândia/MG. The semi-structured interview was the methodological approach chosen for data collection, supported by the record field notebook as a contributor to the ongoing process of reflection. Data analysis was based on proposals of discourse analysis informed by social constructionist perspective. The analysis included a transcript of all interviews, followed by your reading, allowing the identification of interpretative repertoires. Five repertoires were identified: (1) Friendship-Babado, (2) Friendship-Batalha, (3) Friendship-Family, (4) Friendship- Secret and (5) Friendship-Uó. The use of repertoires possible to consider the relationships between the different arrangements that transvestites in turn shape the way you tell about transvestites in this universe, either positively or legitimizing sense of marginality and stigma they share. These senses create, so the possibility of existence between them and, therefore, collaborate and work in the grounds of policies targeted at this population.